Prevalence of anaemia among school adolescent girls. - Goyal, Neha; Rawat, C.M.S; Jha, Sanjay Kumar (Indian Journal of Community Health, 2015)
Background: Anaemia is a major public health problem especially among adolescent females and can result in diminished physical growth and cognitive development, performance in school and at work, and affects reproduction. Findings from NFHS-3 (2005-06) indicate that 56% of the adolescent girls in India are anaemic and, of these 17% suffer from moderate to severe anaemia. Aim & Objective: To find the prevalence of anaemia among adolescent girls in rural and urban schools of Haldwani. Materials and Methods: A cross-sectional study was carried out in rural as well as urban schools of Haldwani from October 2012 to March 2014 among 770 (443 rural and 327 urban) adolescent girls selected by multistage random sampling, using predesigned and pretested questionnaire to collect relevant data, and estimating haemoglobin concentration using Haemoglobin Colour Scale. Data was analysed by using SPSS v 20. Results: 48.18% of adolescent girls were found to have anaemia. Prevalence of anaemia was 43.11% and 55.04% among rural and urban school girls respectively. Mean haemoglobin concentration of study subjects was 11.35g/dl. Prevalence of mild, moderate and severe anaemia among study population was 34.53%, 10.13% and 3.52% respectively. Conclusion: The present study revealed that half of the school going adolescent girls were suffering from anaemia in rural and urban areas of Haldwani